The role of the oxytocin system in the resilience of patients with breast cancer - Liu, Shaochun; Huang, Runze; Li, Anlong; Yu, Sheng; Yao, Senbang; Xu, Jian; Tang, Lingxue; Li, Wen; Gan, Chen; Cheng, Huaidong (Frontiers in Oncology, 2023)
Breast cancer is a grave traumatic experience that can profoundly compromise patients’ psychological resilience, impacting their overall quality of life. The oxytocin system represents one of the essential neurobiological bases of psychological resilience and plays a critical role in regulating resilience in response to social or traumatic events during adulthood. Oxytocin, through its direct interaction with peripheral or central oxytocin receptors, has been found to have a significant impact on regulating social behavior. However, the precise mechanism by which the activation of peripheral oxytocin receptors leads to improved social is still not completely comprehended and requires additional research. Its activation can modulate psychological resilience by influencing estrogen and its receptors, the hypothalamic-pituitary-adrenal axis, thyroid function, 5-hydroxytryptamine metabolism levels, and arginine pressure release in breast cancer patients. Various interventions, including psychotherapy and behavioral measures, have been employed to improve the psychological resilience of breast cancer patients. The potential effectiveness of such interventions may be underpinned by their ability to modulate oxytocin release levels. This review provides an overview of the oxytocin system and resilience in breast cancer patients and identifies possible future research directions and interventions.